Eumelanin–Fe3O4 hybrid nanoparticles for enhanced MR/PA imaging-assisted local photothermolysis. (1st February 2018) - Wang, Junqing; Liu, Heng; Liu, Yu; Chu, Chengchao; Yang, Youyuan; Zeng, Yun; Zhang, Weiguo; Liu, Gang
Abstract : In this work, we report on biodegradable eumelanin–Fe3 O4 hybrid nanoparticles (euMel–Fe3 O4 NPs) for multiple imaging-assisted local photothermolysis. Abstract : In this work, we report on biodegradable eumelanin–Fe3 O4 hybrid nanoparticles (euMel–Fe3 O4 NPs) for multiple imaging-assisted local photothermolysis. The euMel–Fe3 O4 NPs are rationally prepared via a facile one-step co-precipitation method in the aqueous phase in the presence of eumelanin. The obtained NPs exhibited high stability and aqueous dispersity. euMel–Fe3 O4 NPs could provide T 2 -weighted magnetic resonance (MR) and photoacoustic (PA) imaging contrast enhancement prior to the treatment, due to their high r 2 relaxivity that was determined to be 245.88 mM −1 s −1 (a value higher than those for other commercially available iron oxide NPs) and good PA signal intensity. Besides, with effective NIR absorbance, the euMel–Fe3 O4 NPs promoted an effective photothermolysis treatment in an experimental mouse model of cancer. Cytotoxicity and in vivo histological examination demonstrated no appreciable toxicity. Our work suggests that euMel–Fe3 O4 NPs could be proposed as a potential class of theranostic nanoplatform with multiple imaging modalities for cancer therapy.